2016
DOI: 10.1001/jama.2016.9389
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stimulation for In Vitro Fertilization and Long-term Risk of Breast Cancer

Abstract: IMPORTANCE Previous studies of breast cancer risk after in vitro fertilization (IVF) treatment were inconclusive due to limited follow-up. OBJECTIVE To assess long-term risk of breast cancer after ovarian stimulation for IVF. DESIGN, SETTING, AND PARTICIPANTS Historical cohort (OMEGA study) with complete follow-up through December 2013 for 96% of the cohort. The cohort included 19 158 women who started IVF treatment between 1983 and 1995 (IVF group) and 5950 women starting other fertility treatments between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Most recent studies have not shown an association between breast cancer and fertility medication use when comparing women undergoing fertility treatment to both a general population and infertile controls [33] [12] [34] [35] [36]. Although two recent studies found an association of fertility treatment with breast cancer, the increased risk was modest [37] [38].…”
Section: Other Gynecologic Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent studies have not shown an association between breast cancer and fertility medication use when comparing women undergoing fertility treatment to both a general population and infertile controls [33] [12] [34] [35] [36]. Although two recent studies found an association of fertility treatment with breast cancer, the increased risk was modest [37] [38].…”
Section: Other Gynecologic Cancersmentioning
confidence: 99%
“…A recent cohort study of 19,158 IVF patients and 5,950 nonIVF-related patients receiving fertility treatment compared breast cancer risk to the general population with a median follow-up of 21.1 years. No increased risk of breast cancer occurred in IVF patients compared to either the general population (SIR: 1.01, 95% CI 0.93–1.09) or nonIVF-related patients receiving fertility treatment (HR: 1.01, 95% CI 0.86–1.19) [33]. These data agree with a recent meta-analysis of 8 cohort studies that comprised 1,554,332 women and 14,961 breast cancer cases and demonstrated no increased risk of breast cancer in IVF patients versus the general (RR: 0.91, 95% CI 0.74–1.11) or infertile female population (RR: 1.02, 95% CI 0.88–1.18) [37].…”
Section: Other Gynecologic Cancersmentioning
confidence: 99%
“…In addition, clinicians have been wary of potential complications with increasing doses of gonadotropins, particularly OHSS (11,12). There is also concern about the potential association between the use of ovarian stimulants and cancer (13)(14)(15), although, reassuringly, a recent large Dutch study did not find an association between breast cancer and IVF (16).…”
mentioning
confidence: 99%
“…Two of the three studies found significant increases in breast cancer risk among certain subpopulations, such as those who took clomiphene or those who remained nulligravid (Brinton et al, 2014) or only in those who had IVF at a young age (Stewart et al, 2012). A recent study by Van den Belt-Dusebout et al (2016), however, found no significant increase in breast cancer risk. In this study, among women undergoing fertility treatment in the Netherlands between 1983 and 1995, IVF treatment compared with non-IVF treatment was not associated with increased risk of breast cancer after a median followup of 21 years.…”
Section: Introductionmentioning
confidence: 96%